Isolated spina bifida aperta: prenatal ventriculomegaly as an ultrasound prognostic marker. (16th July 2019) - Giardini, Valentina; Verderio, Maria; Cozzolino, Sabrina; Vergani, Patrizia
Abstract : What's already known about this topic? Ventriculomegaly (VMG) is an indirect, variable, and often late cranial sign of spina bifida aperta (SBA). The exact incidence and pathogenesis are unknown: the association between the level of the spinal defect and VMG is controversial, and the incidence of postnatal shunt placement varies widely in the published literature. Prenatal surgery for SBA improves the outcome for children affected by this condition, but it is associated with maternal complications and prematurity which may impact negatively on cognitive outcome. For this reason, the benefit of in utero closure is still matter of debate, and the selection of optimal candidates remain controversial. What does this study add? Early onset ventriculomegaly (VMG) occurring before 24 weeks is significantly associated with high spinal defects and severe VMG at the end of pregnancy. Therefore, it could be an ultrasound prognostic marker for prenatal counselling and an additional criterion in triaging cases for fetal surgery.